A conceptual model of diagnostic system for monitoring stingless bee colony rehabilitation - Yang, Lejing; Haizan Nor, Rozi Nor; Yah Jusoh, Yusmadi; Abdul Malik, Noreha; Wan Mohd Adnan, Wan Nur Asiah (UPM Press, 2025)
The role of stingless bee colonies in ecosystems is crucial, especially their contribution to pollination. However, these bee colonies face multiple threats, such as disease and environmental changes, which could affect their health and numbers. Therefore, it is particularly important to monitor and maintain these colonies to support the stability of the ecosystem and the sustainable development of agriculture. To address this challenge, this paper proposes a new diagnostic system model designed to monitor and promote the rehabilitation of stingless bee colonies. Model of a diagnostic system for monitoring the stingless bee colony rehabilitation. The system uses a DHT11 sensor to monitor temperature and humidity, a load cell to track the hive’s weight, and a force sensor to detect pressure or possible intrusion. Preliminary results show that the system can effectively capture key environmental parameters, providing valuable insights into the rehabilitation process. The findings provide avenues for further research and development of more robust monitoring solutions. This study’s key contribution is combining advanced electronic information engineering techniques with ecological knowledge from previous literature. The proposed conceptual framework is an application of technical tools and a comprehensive approach to understanding and protecting these important ecosystem components. The findings highlight the importance of environmental factors for stingless bee rehabilitation and overall colony health. Environmental parameters such as temperature, humidity, and air quality are critical to the survival and development of bee colonies, directly affecting their reproduction, food supply, and disease transmission.